2018
DOI: 10.5114/hm.2018.76082
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two additional dry-land active warm-up protocols on the 50-m front-crawl swimming performance

Abstract: Purpose. The purpose of the study was to compare the effectiveness of 2 different dry-land active warm-up protocols on 50-m front-crawl swimming performance, biomechanical variables (stroke rate, stroke length, and stroke index), rate of perceived exertion, and exercise heart rate in swimmers of both genders. Methods. The total of 10 male and 9 female national-level swimmers completed a standardized 1000-m in-water warm-up protocol followed by a 30-min transition phase and a 50-m front-crawl time-trial. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 18 publications
0
11
0
11
Order By: Relevance
“…Again, these authors [ 47 ] suggested that the combination of in-water warm-up and dry land exercises was a valuable strategy for maintaining elevated pre-competition core and muscle temperature, thus improving sprint swimming performance [ 2 ]. Subsequently, Dalamitros et al [ 45 ], compared the effects of an in-water warm-up, with the same warm-up followed by: i) 2 × 3 repetitions of ballistic exercises (med ball throw downs, box jumps and crunches), or by ii) dynamic whole body stretching exercises with a work to rest ratio of 10:10 s. After 10 min of rest, the results in 50-m front crawl showed improvements in men after the protocol including dryland exercises. By contrast, women performed better after the protocol including dynamic stretching exercises.…”
Section: Resultsmentioning
confidence: 99%
“…Again, these authors [ 47 ] suggested that the combination of in-water warm-up and dry land exercises was a valuable strategy for maintaining elevated pre-competition core and muscle temperature, thus improving sprint swimming performance [ 2 ]. Subsequently, Dalamitros et al [ 45 ], compared the effects of an in-water warm-up, with the same warm-up followed by: i) 2 × 3 repetitions of ballistic exercises (med ball throw downs, box jumps and crunches), or by ii) dynamic whole body stretching exercises with a work to rest ratio of 10:10 s. After 10 min of rest, the results in 50-m front crawl showed improvements in men after the protocol including dryland exercises. By contrast, women performed better after the protocol including dynamic stretching exercises.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies compared multiple warm-ups to each other, and thus, there were more values for effect sizes [ 3 , 8 , 11 , 12 , 21 , 22 ]. The most complex study was by Kafkas et al [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…In half the studies (n = 7), it was concluded that swimmers performed significantly better after a regular warm-up than over a shorter or dryland warm-up [ 4 , 6 , 7 , 11 , 12 , 21 , 22 ]. However, a warm-up had a small effect on time trial performance across most studies [ 3 , 6 , 7 , 8 , 11 , 15 , 16 , 17 , 18 , 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic warmups have become increasingly popular, and recently published literature has demonstrated increases in subsequent performance [13]. Furthermore, dynamic stretching involves controlled movement through the active range of motion for a joint [14], while crawl stroke speed improvement in 50-meters time-trial performances was demonstrated in male swimmers after active dryland warm-up [15].…”
Section: Introductionmentioning
confidence: 99%